A STUDY OF THE UNITED NATION AND ITS ROLE IN DEVELOPMENT - KAMLESHWAR PRASAD (International Journal of Multidisciplinary Research and Studies, 2020)
The United Nations' primary focus is shifting away from dealing with interstate conflict and toward preventing crimes committed against civilian populations. Ramesh Thakur investigates the evolution of United Nations operations and analyses the organization's shifting function and organizational structure in this book. He raises the questions of why, when, and how it is permissible to employ force, and he contends that the widening gap between legality and legitimacy is evidence of a deteriorating sense of international community. He thinks about the competition that exists between the United States of America, which has the ability to employ force and project power, and the United Nations, which is the core of the international legal system. He maintains that the rule of law and a rules-based order centred on the United Nations are the cornerstones of a civilised system of international relations, and that they are of the utmost central importance. Students of the United Nations and other international organisations studying in departments of politics, law, and international relations will find this book to be of interest.